Areas for wheat seed production in Central High Valleys of Mexico - Acuayte-Valdés, Erik; Sandoval-Islas, Sergio; Carballo-Carballo, Aquiles; Villaseñor-Mir, Eduardo; Leyva-Mir, Santos Gerardo; Vargas-Hernández, Mateo (Revista Mexicana de Ciencias Agrícolas, 2018)
The agro-ecological zoning allowed to define localities with aptitude for the establishment of the wheat crop, as well as the areas that present conditions not favorable for the development of spike blight disease by Fusarium sp. (TEF) which causes weight reduction in grains and contamination by mycotoxins, among which is deoxynivalenol (DON). In general, agricultural production is determined by combinations of climate and soil characteristics. For wheat, it was considered as optimal temperature 15 to 23 °C, precipitation 750 to 900 mm, and altitude 4 500 meters above sea level, TEF depends mainly on the interaction of climatic factors and genotype. The climatic thresholds considered were those reported to intensify the Relative Disease Index: minimum temperature greater than 11 ºC, average temperature higher than 16.5 ºC, thermal oscillation lower than 13.4 ºC and rainfall greater than 30 mm. Potential areas were geographically and quantitatively delimited taking into account the criteria that define places and surfaces climatically suitable for the cultivation of rainfed wheat (may to October) and not suitable for TEF, making a discrimination of urban areas and other uses that do not be the agricultural, therefore the map generated can be used as a planning tool for the establishment of wheat cultivation, extension of areas and renewal of plantations for seed production in the Central High Valleys of Mexico.
Keywords: Fusarium sp.; Agrometeorology; deoxynivalenol; spike blight; zoning.